FREQUENCY OF VITAMIN D DEFICIENCY IN PATIENTS WITH FATIGUE. - Rizwan Rasul Khan; Khalid Mehmood Yahya; Ali Saqib (Journal of University Medical & Dental College, 2014)
ABSTRACT: OBJECTIVE: To study vitamin D status in patients presenting with complaint of easy fatigability and also its prevalence in relation to common contributors to this complaint which may manifest without any physical sign e.g. new onset Diabetes mellitus and Chronic Hepatitis B and C. SETTINGS AND DURATION: This descriptive study was conducted at medical outpatient clinic at Chinniot General Hospital and Madinah Teaching Hospital from March to May 2012 in patients coming from Faisalabad and its suburbs. MATERIAL AND METHOD: This study included 100 patients with age limit 16 to 60 years. Sample population included only those patients who neither had a known disease, physical or psychological nor any sleep disorder that could contribute to their complaint of easy fatigability. Organic diseases that could contribute to fatigue were carefully ruled out by clinical examination. For each patient, random blood glucose level, hepatitis B surface antigen (HBsAg) and hepatitis C antibody (anti HCV) and 25Hydroxy D levels (25OHD) were done. RESULTS: Out of 100 patients, 92 were found to have low Vitamin D levels. Only 8 were found to have Vitamin D status in the normal range and these included all females. 86 patients were Vitamin D deficient, one third of who in were having severe deficiency with almost equal gender distribution. Among Vitamin D deficient cases, 2/3rd belonged to female gender. 6 patients had vitamin D insufficiency and none had vitamin D level above the normal range. Furthermore, none had optimal Vit D level. Only 18 patients were found to be anti HCV positive and 12 patients were HBsAg positive, both with equal gender distribution. High blood glucose level was observed in 12 patients out of whom, 75% were found to have random blood glucose level > 200mg /dL and rest had impaired glucose tolerance. CONCLUSION: Prevalence of Vitamin D deficiency is alarmingly high in patients presenting with fatigue, even more than that seen in other parts of the world. Furthermore relative frequencies of Chronic Hepatitis B & C and Diabetes mellitus are much less as compared to that of vitamin D deficiency, despite Pakistan being declared a “cirrhotic state” where Diabetes mellitus is an “epidemic”.28